Benchmarking of solar irradiance nowcast performance derived from all-sky imagers. (November 2022) - Logothetis, Stavros-Andreas; Salamalikis, Vasileios; Wilbert, Stefan; Remund, Jan; Zarzalejo, Luis F.; Xie, Yu; Nouri, Bijan; Ntavelis, Evangelos; Nou, Julien; Hendrikx, Niels; Visser, Lennard; Sengupta, Manajit; et al.
Abstract: Fluctuations of the incoming solar irradiance impact the power generation from photovoltaic and concentrating solar thermal power plants. Accurate solar nowcasting becomes necessary to detect these sudden changes of generated power and to provide the desired information for optimal exploitation of solar systems. In the framework of the International Energy Agency's Photovoltaic Power Systems Program Task 16, a benchmarking exercise has been conducted relying on a bouquet of solar nowcasting methodologies by all-sky imagers (ASI). In this paper, four ASI systems nowcast the Global Horizontal Irradiance (GHI) with a time forecast ranging from 1 to 20 min during 28 days with variable cloud conditions spanning from September to November 2019 in southern Spain. All ASIs demonstrated their ability to accurately nowcast GHI, with RMSE ranging from 6.9% to 18.1%. Under cloudy conditions, all ASIs' nowcasts outperform the persistence models. Under clear skies, three ASIs are better than persistence. Discrepancies in the observed nowcasting performance become larger at increasing forecast horizons. The findings of this study highlight the feasibility of ASIs to reliably nowcast GHI at different sky conditions, time intervals and horizons. Such nowcasts can be used either to estimate solar power at distant times or detect sudden GHI fluctuations. Highlights: ASI-based GHI nowcasts outperform persistence model under cloudy conditions. Under clear skies, three ASIs reveal more accurate nowcasts than persistence. ASIs forecasts are more accurate from persistence at increasing forecast horizons.